Esofagopatia chagásica complicada com esôfago de Barrett - Monteiro Machado, Wellington [UNESP]; Padula Neto, Pedro [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP] (My University, 2003)
Gastroesophageal reflux disease (GERD) is an uncommon condition in chagasic esophagopathy not previously treated. In this report, a case of chagasic esophagopathy associated to GERD and complicated with Barrett's esophagus is described. Potential pathophysiologic mechanisms underlying the condition are presented and commented.
Chagasic esophagopathy complicated with Barrett's esophagus
Keywords: Barrett' esophagus; Chagas' disease; Chagasic esophagopathy; Gastroesophageal reflux disease; Megaesophagus; adult; Barrett esophagus; case report; Chagas disease; esophagoscopy; gastroesophageal reflux; human; lower esophagus sphincter; male; megaesophagus